2019
DOI: 10.1186/s12864-019-5905-9
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and conservation of polycomb repressive complex 1 core components and putative associated factors in the green lineage

Abstract: Background: Polycomb group (PcG) proteins play important roles in animal and plant development and stress response. Polycomb repressive complex 1 (PRC1) and PRC2 are the key epigenetic regulators of gene expression, and are involved in almost all developmental stages. PRC1 catalyzes H2A monoubiquitination resulting in transcriptional silencing or activation. The PRC1 components in the green lineage were identified and evolution and conservation was analyzed by bioinformatics techniques. RING Finger Protein 1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 109 publications
(177 reference statements)
1
22
2
Order By: Relevance
“…We demonstrate that EPR-1 forms nuclear foci, reminiscent of Polycomb bodies (24), and its genomic distribution is limited to, and dependent upon, H3K27-methylated chromatin, which it recognizes directly through its BAH domain. Finally, we discover that EPR-1 orthologs are widely distributed across eukaryotes, contrary to previous reports (21,25,26), suggesting an ancient role of EPR-1 homologs in Polycomb repression that was then lost on multiple occasions in certain lineages.…”
Section: Introductioncontrasting
confidence: 94%
“…We demonstrate that EPR-1 forms nuclear foci, reminiscent of Polycomb bodies (24), and its genomic distribution is limited to, and dependent upon, H3K27-methylated chromatin, which it recognizes directly through its BAH domain. Finally, we discover that EPR-1 orthologs are widely distributed across eukaryotes, contrary to previous reports (21,25,26), suggesting an ancient role of EPR-1 homologs in Polycomb repression that was then lost on multiple occasions in certain lineages.…”
Section: Introductioncontrasting
confidence: 94%
“…We demonstrate that EPR-1 forms nuclear foci, reminiscent of Polycomb bodies (24), and its genomic distribution is limited to, and dependent upon, H3K27-methylated chromatin, which may be recognized through its BAH domain. Finally, we discovered that EPR-1 orthologs are widely distributed across eukaryotes, contrary to previous reports (21,25,26), suggesting an ancient role of EPR-1 homologs in Polycomb repression that was then lost on multiple occasions in certain lineages.…”
contrasting
confidence: 96%
“…6A). Notably, we determined the Arabidopsis thaliana paralogs EBS and SHL as orthologs of EPR-1 in our analyses, which have been erroneously reported as plant-unique proteins (21,25,26). Similar to EPR-1, the plant paralogs, EBS and SHL, bind H3K27 methylation and have been implicated in gene repression (17,18,21).…”
Section: Epr-1 Is a Homolog Of Plant Ebs/shl And Widely Distributed Amentioning
confidence: 99%
“…from Tetrahymena thermophila and a phosphorylated histone H3 peptide (aa. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] showed that the HAT domain interacts with the sidechain of glutamine 5 (Q5), located 9 amino acids upstream of the target lysine (K14) on the H3 peptide (56). As H3K27 is similarly located 9 amino acids upstream H3K36, this suggests that the HAT domain of GCN5 in Arabidopsis may interact with the sidechain of H3K27 to regulate the catalytic activity of GCN5 at H3K36.…”
Section: Discussionmentioning
confidence: 99%